LABOUR BANKS FOR SUSTAINABLE AGRICULTURAL DEVELOPMENT-AN ENQUIRY INTO THE DETERMINANTS AND BARRIERS OF JOINING Indian J Econ Dev - M.Anoop; N.Ajjan and K.R.Ashok
Labour scarcity is emerging as a threat to sustainable agricultural development, which put the farmers as well as consumers in trouble through its widespread ramifications. This study analyses labourer’s joining decision in Labour Banks and barriers for joining. Logistic regression model revealed that experience, and primary occupation status positively influenced labourer’s joining decision in Labour Banks, whereas age negatively influenced the joining decision. Work in distant places and lack of interest were found to be the most important barriers for joining in Labour Banks followed by unsatisfactory work conditions, lack of awareness and working as permanent labourer. The study suggested that proper government support, enhancement of the training programmes so as to provide more skilled labourers to these groups, and replication of this model to other areas after making necessary modifications suited for the local situations, will help to address the issue of lack of availability of skilled labourers in agriculture.